(untitled) (Olhares, 2015)
The article discusses the multidisciplinar work of Daniela Thomas from the concern of dramaturgy of space. The practice expanded by various media such as theater, cinema, fine arts and installations is focused to indicate the structure of multiple spaces created by the artist, expressing the idea of the project in terms of construction of space.